Evaluasi Usability Website Jurnal ABC Menggunakan Metode Usability Testing - Muhamad Rizky (Pusat Riset dan Inovasi Nasional, 2024)
Website-based public services are certainly an important part of supporting the success of a higher education institution, one of which is a journal website for the publication of scientific articles for lecturers and students. However, many of these website-based services are still difficult to use and do not function well. This research was conducted to evaluate whether the ABC Journal website has usability testing acceptability criteria and find out how much user acceptance the website has. The method used in this research is the Usability Testing method. Based on the results of data processing, the average value of the overall usability test to measure the use of the ABC Journal website for the Learnability aspect was 3.25, Efficiency was 3.30, Memorability was 3.20, Errors were 3.28 and Satisfaction was 3.23. These results show that the ABC Journal website is quite easy to use. Suggestions to the administrator of the ABC Journal Website, to increase the value of each aspect of usability so that it can be easy to use for its users.